Reproducing Fictional Ethnographies Surrogacy and Digitally Performed Anthropological Knowledge - Apostolidou, Anna. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
"An exciting and groundbreaking project that links experimental writing and multimodal ethnography to some of the most important contemporary theoretical and methodological debates in anthropology and beyond, while making a compelling and urgent case for ethnographic research as a form of creative practice and worldly engagement." -Stuart McLean, Professor of Anthropology, University of Minnesota, USA This book focuses on the example of surrogate motherhood to explore the interplay between new reproductive technologies and new ethnographic writing technologies. It seeks to interrogate the potential of fictional multimodality in ethnography and to illuminate the generative possibilities of digital artefacts in anthropological research. It also makes a case for the tailor-made character of ethnographic writing in the digital era, arguing that research quests and representational modalities can be paired together to develop unique narrative forms, corresponding to each particular topic's traits and analytical affordances. Focusing on the intersections of assisted reproduction technologies and digitally mediated writing, this study casts light upon the value of the affective, the fictional and the 'real' in the anthropological research and writing of relatedness. Analyzing the situated knowledge of ethnographers and research interlocutors, it experiments with multimodal storytelling and revisits the century-long debate on the affinity between an object of study and the possibilities for its representation. As the first attempt to bring together digital anthropology, fiction writing and the ethnography of surrogacy, this book fuses the genealogy of feminist critique on the orthodox, phallocentric, and heteronormative aspects of academic discourse with the input of digital humanities vis-à-vis troubling the conventional formal properties of scholarly writing. Anna Apostolidou holds a PhD in social anthropology (University College London) and a PhD in digital education (Hellenic Open University). She has taught, conducted research and published extensively on gender and sexuality, digital learning, refugee education, surrogate motherhood and fictional digital writing.
1. Surrogate Bodies and Digital Critique -- 2. The Literary and the Ethnographic: Fictionalizing Surrogacy -- 3. Assisted Reproduction as Poetry and Metaphor -- 4. When Fictional Ethnography Goes Digital -- 5. Epilogue: Un-Disciplining Anthropology.
Keywords: Anthropology and the arts; Ethnology; Human body-Social aspects; Feminism; Feminist theory; Anthropology of the Arts; Ethnography; Sociology of the Body; Sociocultural Anthropology; Feminism and Feminist Theory